Screening of fluoroquinolone residues in imported and locally produced broiler chicken meat in Ibadan, Nigeria (International Journal of Health, Animal Science and Food Safety, 2014)
The study was conducted to investigate residues of three fluoroquinolones (ciprofloxacin, norfloxacin and ofloxacin) in chicken meat sold in Ibadan, Nigeria. Two hundred and ninety-seven (297) samples of imported frozen (99) locally produced frozen (99) and freshly slaughtered (99) broiler chicken meat products were screened for antibiotic residues by microbiological assay using Escherichia coli as test organism. High performance liquid chromatography (HPLC) with ultraviolet (UV) detection was used for the determination of ciprofloxacin, norfloxacin and ofloxacin in the positive samples. One hundred and sixty (160) samples, constituting more than half (53.87%) of total sample size tested positive for Escherichia coli–sensitive antibiotic residues.  Positive samples were 54.55%, 56.57% and 52.53%, of freshly slaughtered, locally produced frozen chicken and imported frozen chicken meat respectively. Residues of investigated fluoroquinolones occurred more frequently in locally produced frozen chicken than in imported frozen chicken. The concentrations were however consistently higher in imported chicken. Among the three fluoroquinolones examined, the most abundant in imported frozen chicken was ciprofloxacin with mean 354.83±716.43µg/kg. Norfloxacin was the most abundant in freshly slaughtered and locally produced frozen chicken meat, having mean values of 107.70±138.36µg/kg and 120.96±162.83µg/kgrespectively while ofloxacin was the lowest in all categories. Most frozen chicken products imported into Nigeria at the time of this study contain higher levels of residual fluoroquinolones than the locally produced chicken. In order to tackle fluoroquinolone resistance from a food safety perspective, proper usage and monitoring of fluoroquinolones in meat animals should be encouraged in developing countries.
Keywords: Fluoroquinolones; Residues; Chicken; Antibiotic resistance; Nigeria